Efectiveness of kenitu leaf extract (chyrysophyllum cainito l.) on bone density and histopathology osteoblast-osteoklast in female mice - Pare, Nurdiana Tandi; Widodo, Gunawan Pamudji; Iswandi, Iswandi (Institute of Computer Science (IOCS), 2025)
Osteoporosis is a systemic bone disease characterized by a decrease in bone density and deterioration of bone microarchitecture so that bones become brittle and break easily. Osteoporosis due to long-term use of glucocorticoids causes osteoporosis. There is a lot of clinical evidence about the role of phytoestrogens in the treatment of osteoporosis. Kenitu (Chrysophyllum cainito) contains isoflavone phytoestrogen compounds. The aim of this research was to determine the anti-osteoporosis effect of ethanol extract of kenitu leaves (Chrysophyllum cainito L.), by looking at the increase in bone density as well as the number of osteoblast cells and the number of osteoclast cells in the femur trabecular bone of female mice induced by dexamethasone. In this study, 49 female mice were grouped into 7 groups, namely normal control, negative control, positive control with cabone naturindo, and groups treated using 70% ethanol extract of kenitu leaves with varying doses of 100 mg/kg BW, 200 mg/kg BW, 400 mg/kg BW and 800 mg/kg BW. An increase in femur trabecular bone density, the number of osteoblast cells and the number of osteoclast cells were observed using the Histomorphometry method. The results showed that the ethanol extract of kenitu leaves has anti-osteoporosis activity. The ethanol extract of kenitu leaves has a dose of 400 mg/kg BW which is the optimal dose as anti-osteoporosis which is indicated by an increase in bone density, an increase in the number of osteoblast cells and a decrease in the number of osteoclast cells.